2011
DOI: 10.1055/s-0031-1297253
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Combined Triiodothyronine (LT3) and Thyroxine (LT4) Treatment in Athyreotic Patients Unresponsive to LT4 Alone

Abstract: Despite some reports, the usefulness of levothyroxine (LT(4)) and levotriiodothyronine (LT(3)) combination therapy in hypothyroidism remains controversial. The objective of this paper is to study a benefit of additional LT(3) in athyreotic patients who failed to normalize TSH on LT(4) alone even with hyperthyroid serum T(4) values. In a survey of 200 athyreotic patients treated between 2006 and 2009, about 7% failed to normalize serum TSH levels following treatment with LT(4), though serum T(4) values in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Three remarkable phenomena have been observed in l -T4-treated patients, (1) a dissociation between FT3 and FT4, (2) a disjoint between TSH and FT3, and (3) an l -T4-related conversion inefficiency ( 121 , 123 ). Hence, l -T4 dose escalation may not invariably remedy T3 deficiency but could actually hinder its attainment ( 121 , 201 ). In addition to substrate inhibition and an inhibitory action of reverse T3 on the enzyme activity of deiodinase type 2, experimental studies in the rat elaborate on molecular details involving ubiquitination that may explain a lack of effect of increasing T4 dose in this condition ( 64 ).…”
Section: Homeostatic Considerations In T4-treated Patientsmentioning
confidence: 99%
“…Three remarkable phenomena have been observed in l -T4-treated patients, (1) a dissociation between FT3 and FT4, (2) a disjoint between TSH and FT3, and (3) an l -T4-related conversion inefficiency ( 121 , 123 ). Hence, l -T4 dose escalation may not invariably remedy T3 deficiency but could actually hinder its attainment ( 121 , 201 ). In addition to substrate inhibition and an inhibitory action of reverse T3 on the enzyme activity of deiodinase type 2, experimental studies in the rat elaborate on molecular details involving ubiquitination that may explain a lack of effect of increasing T4 dose in this condition ( 64 ).…”
Section: Homeostatic Considerations In T4-treated Patientsmentioning
confidence: 99%
“…While LT4 dose escalation or the use of liquid formulations effectively control elevated TSH levels in various conditions including gastric problems, intestinal malabsorption, or drug interference (103, 104), this situation is different, as low FT3 concentrations persist in these patients despite suppressed TSH levels and elevated FT4 concentrations (102). Apparently, a minority of patients on LT4 still fail to concomitantly raise their serum FT3 concentrations as the T4 excess itself impairs T3–T4 conversion (102, 105). The clinical relevance was recently confirmed as euthyroid TSH targets could not adequately raise resting energy expenditure (REE) adjusted for lean body mass in LT4-treated women, compared to healthy controls, only FT3 levels being positively correlated with REE (106).…”
Section: Interrelational Measures and Emerging New Concepts Of Thyroimentioning
confidence: 99%
“…Observational data from these patients suggested that the addition of T3 reduced TSH and FT4 and increased FT3. 57 Real world evidence is used increasingly by regulators and other clinical experts to evaluate the effects of therapeutic interventions in the routine clinical setting outside the restrictions of randomised clinical trials. Such studies are inherently prone to bias, however, and their results should be interpreted with caution.…”
Section: Real World Evidencementioning
confidence: 99%